Advances on terahertz single-pixel imaging - Hu, Qiao; Wei, Xudong; Pang, Yajun; Lang, Liying (Frontiers in Physics, 2022)
Single-pixel imaging is a novel imaging technique that can obtain image information through a single-pixel detector. It can effectively avoid the problem of lack of high-quality area array detectors in the terahertz band, and has attracted the attention of a large number of researchers in recent years. In this paper, the basic imaging principles, terahertz beam modulation methods and typical image reconstruction algorithms for terahertz single-pixel imaging are introduced and discussed, as well as its research progresses and developing trends.